Living in Cohousing Communities: Psychological Effects and Coping Strategies in Times of COVID-19 - Christian Schetsche; Luis Carlos Jaume; Lucas Gago-Galvagno; Ángel Elgier (Interpersona: An International Journal on Personal Relationships, 2020)
The aim of this study was to compare a sample of residents in cohousing communities (n = 180) and inhabitants in traditional neighborhoods (n = 104). During the social isolation that was decreed by the German government due to the COVID-19 pandemic, data collection was carried out through the Internet. Psychological symptoms and coping strategies were measured, and their differences were investigated by multivariate analysis of variance (MANOVA). Results showed that residents in cohousing communities have lower levels of depressive, anxiety, compulsive and eating disorders, as well as less use of coping strategies which are based on emotional concealment, problem avoidance, and social withdrawal. Moreover, its inhabitants showed higher levels in the use of social support. It is concluded that living in a cohousing community favors, in comparison with life in traditional neighborhoods, the mental health of its inhabitants.